Small-molecule affinity capture of DNA/RNA quadruplexes and their identification in vitro and in vivo through the G4RP protocol. Issue 11 (5th April 2019) - Renard, Isaline; Grandmougin, Michael; Roux, Apolline; Yang, Sunny Y; Lejault, Pauline; Pirrotta, Marc; Wong, Judy M Y; Monchaud, David
Abstract: Guanine-rich DNA and RNA sequences can fold into higher-order structures known as G-quadruplexes (or G4-DNA and G4-RNA, respectively). The prevalence of the G4 landscapes in the human genome, transcriptome and ncRNAome (non-coding RNA), collectively known as G4ome, is strongly suggestive of biological relevance at multiple levels (gene expression, replication). Small-molecules can be used to track G4s in living cells for the functional characterization of G4s in both normal and disease-associated changes in cell biology. Here, we describe biotinylated biomimetic ligands referred to as BioTASQ and their use as molecular tools that allow for isolating G4s through affinity pull-down protocols. We demonstrate the general applicability of the method by purifying biologically relevant G4s from nucleic acid mixtures in vitro and from human cells through the G4RP-RT-qPCR protocol. Overall, the results presented here represent a step towards the optimization of G4-RNAs identification, a key step in studying G4s in cell biology and human diseases.